Analisis Metode Harga Pokok Pesanan Terhadap Penentuan Harga Pokok Produksi Pada PT XYZ - Ranteallo, Asrah Tandirerung; Firdaus, Salsabila (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research investigates the impact of job order costing method on determining the cost of production at PT XYZ. Two main methods, namely full costing and variable costing, were analyzed to evaluate the differences in production cost estimates. The findings suggest that full costing tends to yield lower production costs compared to variable costing, primarily due to the inclusion or exclusion of fixed factory overhead costs. Evaluation of both methods highlights the importance of a deep understanding of the company's cost structure in accounting decision-making. Recommendations for PT XYZ include continuous evaluation of the effectiveness of both methods, development of a better cost tracking system, and exploration of the use of method combinations to meet the company's specific needs.